Effect of Giving Tofu Dregs Bokashi on Phosphate Dynamics in Ultisols - Alisa Norhalimah; J. Jumar; Nukhak N.S (Universitas Sembilanbelas November Kolaka, 2022)
Ultisols are soil types that are poor in nutrients, one of which is element P, where this nutrient is needed by plants in large quantities. In Ultisols, P nutrients are bound by Al, so the availability of P nutrients for plants is low. Giving organic matter is one way to speed up the process of soil amelioration. Tofu waste is organic waste that contains nutrients and can be used as organic fertilizer that can help improve soil nutrients. Tofu dregs contain organic N, P, K, Ca, Mg, and C, which have the potential to increase soil fertility. This study aims to determine the effect of tofu pulp bokashi application on the dynamics of phosphate in Ultisols soil and to obtain the best dose of tofu pulp bokashi on the availability of phosphate in Ultisols soil. The method used in this study was a 1-factor Completely Randomized Design (CRD) with 6 (six) levels of treatment with 3 (three) replications in order to obtain 18 experimental units. Treatment P0 was without giving bokashi, P1 was P fertilizer 200 kg.ha-1, P2 was bokashi tofu dregs 12 t.ha-1, P3 was bokashi tofu dregs 24 t.ha-1, P4 was bokashi tofu dregs 12 t.ha-1 and fertilizer P 200 kg.ha-1, P5 namely bokashi tofu dregs 24 t.ha-1 + fertilizer P 200 kg.ha-1. The results of this study showed that the administration of tofu dregs bokashi had a significant effect and the best dose was obtained for increasing pH and available P by giving bokashi tofu dregs 24 t.ha-1 and P fertilizer 200 kg.ha-1. The best dose to reduce Al-dd is by giving bokashi tofu dregs 24 t.ha-1 and P fertilizer 200 kg.ha-1